A remarkable new species of the genus Ganyopis from Malacca, Malaysia (Curculionidae: Conoderinae, Mecopini) - Pancini, Lorenzo (Fragmenta entomologica, 2024)
Ganyopis notabilis sp. nov. is described and figured. It represents the fourth described species of Ganyopis and the second known from Malacca (Malaysia). Some morphological notes on the genus are also provided.